Supracondylar Humeral Fractures in School Children: Incidence and Aetiology during School Terms and Holidays - Babalola, Olatunji Oladapo; Ugwoegbulem, Orlando Anozie; Izuagba, Emeka Bide; Idowu, Oluwaseyi K.; Owoola, Adebayo Musifiru (Nigerian Journal of Orthopaedics and Trauma, 2020)
Background: Supracondylar humeral fracture is a common injury in the paediatric age group. The morbidity from its complications such as vascular injury, compartment syndrome and malunion can last the entire lifetime of the child if not recognised and managed appropriately. The aim of the study is to determine the mechanisms of injury and to compare the incidence during school term and holiday periods in school age children. Patients and Methods: A descriptive retrospective study was carried out at the paediatric orthopaedic unit of an orthopaedic hospital. All school age children with supracondylar humeral fractures between 1 January 2014 and 31 December 2017 were included in the study. The demographic data, mechanism of injury, date of injury (to determine whether school term or holiday), Gartland classification and the mode of management were recorded. Results: A total of 53 patients were reviewed. The mean age was 5.94 ± 2.71 years, with a male: female ratio of 2.8:1. The most common mechanism of injury was fall from a height (30.2%). The overall incidence was 0.25/week over the 4‑year period school term (0.22/week and holiday period 0.47/week). The extension type of injury occurred in 52 (98.1%) patients with 7 (13.5%), 4 (7.7%) and 41 (78.8%) being Gartland type I, II and III, respectively. Conclusion: The most common mechanism of injury was fall from a height and there was an increased incidence during holiday compared to the school term period. Larger studies on safety strategies during holiday activities may reduce the incidence of humeral supracondylar fractures.